Use of Integrative Oncology, Involvement in Decision-Making, and Breast Cancer Survivor Health-Related Quality of Life in the First 5 Years Postdiagnosis. (September 2018) - Andersen, M. Robyn; Sweet, Erin; Hager, Shelly; Gaul, Marcia; Dowd, Fred; Standish, Leanna J.
Objective: This study sought to describe changes in the health-related quality of life (HRQOL) of women who do and do not seek naturopathic oncology (NO) complementary and alternative medicine (CAM) care during and immediately after breast cancer treatment, and to explore the predictive role of NO CAM care, demographic characteristics, and involvement in decision-making on HRQOL in breast cancer survivors.Methods: Matched cohorts of breast cancer survivors who did and did not choose to supplement their breast cancer treatment with NO care within 2 years of diagnosis participated. NO users were identified through naturopathic doctors' clinics and usual care (UC) controls with similar prognosis were identified through a cancer registry. The registry provided information about all participants' age, race, ethnicity, marital status, stage of cancer at time of diagnosis, date of diagnosis, and use of conventional medical treatments (surgery, chemotherapy, radiation, and endocrine therapy). Data of participants' self-reported involvement in decision-making and HRQOL were collected at study enrollment and at 6-month follow-up.Results: At 6-month follow-up, the NO patients reported significantly more involvement in decision-making about care and better general health than did UC patients ( P < .05). Self-reported involvement in decision-making about cancer treatment was associated with better role-physical, role-emotional, and social-functional well-being ( P < .05). Race, age, marital status, and congruence of preferred and achieved levels of involvement also predicted aspects of HRQOL in breast cancer survivors ( P < .05).Conclusions: Both NO CAM care and involvement in decision-making about cancer treatment may be associated with better HRQOL in breast cancer survivors.